Comprehensive Analysis of Geometric Model of a Variable Thickness Scroll Expander - ZHANG Pengcheng, PENG Bin, MA Jie (Shanghai Jiaotong Daxue xuebao, 2023)
A novel variable thickness scroll expander composed of involutes of circle with different base circle radii is proposed. The generating method of profile is discussed, the general equation of profile is given, and a series of geometric models of the variable thickness scroll expander are established. According to the established geometric model, the influence of control coefficient on the volume change of the variable thickness scroll expander is analyzed. In addition, the geometric models of the traditional equal constant thickness and variable thickness scroll expander are constructed, and the advantages and disadvantages of the geometric models are compared. The results show that the novel variable thickness scroll expander model not only has the advantages of the traditional variable thickness model, but also greatly reduces the amount of calculation. To a certain extent, it enriches the types of variable thickness scroll expanders and provides reference for the development of high-performance scroll expanders.